Epileptic encephalopathy with electrical status epilepticus during slow sleep: evaluation of treatment response from a tertiary center - Kılıç, Betül; Acar, Mecit; Topçu, Yasemin; Turanlı, Güzide (The Turkish Journal of Pediatrics, 2022)
Background. This study aimed to evaluate the clinical, electrophysiological, etiological features, and treatment response in children with epileptic encephalopathy with electrical status epilepticus during slow sleep (ESES). Methods. Clinical data, records of electroencephalograms (EEG), and brain magnetic resonance imaging (MRI) findings of 33 patients with ESES who were treated, and followed up for at least one year were retrospectively analyzed. Results. Of all patients, 57.6% were male, and 42.4% were female. The mean age was 10.45 ± 2.88 years. At first admission, 90% of patients had seizures, and 10% had only school failure. Twelve patients had childhood focal epileptic syndrome. In etiology, asphyxia (n=6), hydrocephalus (n=2), polymicrogyria (n=1), and mesial temporal sclerosis (n=1) were determined. Neurological examination was abnormal in 27.2%, and brain MRI findings were pathological in 36.3% of the patients. During the ESES phase, the spike-wave index (SWI) on the non-rapid eye movement (NREM) sleep EEG was > 85% in 16 patients and 50-85% in 17 patients. Only one patient received one, and the others had at least two antiseizure medications. Benzodiazepines were found to be the most effective treatment. In the two-year follow-up, 24 patients (72.7%) were seizure-free, and nineteen patients (57.5%) had complete recovery of SWI on their NREM sleep EEG. There was a significant correlation with reduction of the SWI on the EEG and seizure control (p < 0.001). In addition, a significant correlation was found between neurocognitive and behavioral scores scored before and after treatment, seizure control, and EEG recovery. Conclusions. ESES is an epileptic encephalopathy that can be treated safely with antiseizure medications. Neurocognitive examinations and follow-up of EEG findings are valuable in terms of the treatment response. Benzodiazepines were found to be very effective in additional treatment.